Implementasi Kegiatan Kokurikuler Di Pendidikan Anak Usia Dini Al-Islam Riyadhul Irfan Kecamatan Kadungora - Aliyah, Siti; Qudsiah, Maria Ilfa; Huda, Nova Nurul (LP2M STAI Al-Musaddadiyah Garut, 2025)
This research is motivated by an initial observation conducted on October 11, 2024, at PAUD Al-Islam Riyadhul Irfan, located in Kp. Babakan RT 02 RW 08, Rancasalak Village, Kadungora District, Garut Regency. Based on the observation results, it was found that extracurricular activities were conducted in the form of performances or activities that required a significant amount of funding. This phenomenon indicates the need for a more in-depth study regarding the implementation of extracurricular activities that align with the operational theory at the PAUD level. The aim of this research is to describe the implementation of extracurricular activities at PAUD Al-Islam Riyadhul Irfan and the obstacles and challenges faced by PAUD Al-Islam Riyadhul Irfan in implementing these activities. This research uses a descriptive qualitative approach with research subjects consisting of the school principal and teachers of PAUD Al-Islam Riyadhul Irfan in Kadungora District. Data collection techniques include observation, interviews, and documentation. Data analysis techniques are carried out through stages of data reduction, data presentation, and drawing conclusions. The research results indicate that the implementation of extracurricular activities is structured and in accordance with the Guidelines for Developing the Pancasila Student Profile Project. Thus, these extracurricular activities can be carried out in a structured manner. The implementation of extracurricular activities at Al-Islam Riyadhul Irfan Early Childhood Education is already in accordance with the established regulations. The implementation of extracurricular activities at Al-Islam Riyadhul Irfan Early Childhood Education has been carefully regulated and follows the applicable guidelines. Keywords: Co-Curricular Activities; Implementation; Early childhood